The Effect of Return on Assets, Effective Tax Rate, and Company Size on Transfer Pricing in Food and Beverage Companies listed on the Indonesia Stock Exchange - Ridwan Ridwan (Indonesian Journal of Economics and Management, 2023)
This study aims to determine and explain the impact of Return on Assets, Effective Tax Rate, and Company Size on Transfer Pricing. This type of research is quantity research. The data used is secondary data obtained from Indonesia Stock Exchange Website. The sample in this study amounted to 10 (ten) companies. Data analysis using path analysis and data processing using IBM SPSS 26.0. The results of this study state that Return on Assets has a negative and significant effect on Transfer Pricing, Effective Tax Rate has a negative and significant effect on Transfer Pricing, the results of this study Company Size has a positive and significant effect on Transfer Pricing, and Return on Assets, Effective Tax Rate, and Company Size has a positive and significant effect simultaneously on Transfer Pricing.